REFLECTION ON THE USE OF DIGITAL STORYTELLING IN SPEAKING CLASS IN THE PANDEMIC TIME - Sumbayak, Desri Maria; Tamala, Indah Putri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2022)
The individual digital storytelling project was given to 129-second semester students of Speaking Class in English Literature Study Program, Faculty of Cultural Sciences, Universitas Sumatera Utara Indonesia during this pandemic time. After a virtual workshop on how to do digital story-telling was given to the students, they were asked to create their video stories. There were two topics given to the students. Students might have the freedom to either tell their own stories or to tell a fable or fairy tale. After doing the project, students were asked to do self-reflection on their project by answering a questionnaire. The questionnaire consists of three closed- questions and three semi-open questions. The result revealed that the majority of the students mentioned that the project was engaging, could improve their speaking skills, and accommodate their creativity. Besides, most of the students argued that the project could enhance their autonomous learning. 126 students out of 129 said that the project was very beneficial to improving their speaking skills even though they had only virtual speaking classes during the pandemic, except there were three students who showed that they needed the in-person feedback from the teacher and the ambiance of the real face to face class. Thus, it is recommended to apply digital storytelling and its implications in online-learning mode.